If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+3=x-3
We simplify the equation to the form, which is simple to understand
4x+3=x-3
We move all terms containing x to the left and all other terms to the right.
+4x-1x=-3-3
We simplify left and right side of the equation.
+3x=-6
We divide both sides of the equation by 3 to get x.
x=-2
| 102=4(6)(3)+2(3)(h) | | 15=4y+11-2 | | 6-4(2-5x)=6-4(-3x) | | 7x-8=14x+8 | | 450-1000=x | | x-3x=3 | | 3x+1+4x-5= | | 143/7= | | 2y+4z=8 | | -1-n=5 | | F(2)=(2)+7 | | 12+5w-4w=5 | | 4+(s+2s)-s=2s-1(12) | | 4(6w+4)*(5-3)=5(3w+9)*4(6w+8) | | 45(-d)=79 | | F(1)=(1)+7 | | y^2+x^2+8y-10x+37=0 | | 3x+x-4=12 | | 54x-7+x=36 | | 3x+x-4=6 | | n-3n=20-4n | | 36+-4c+-3c=22 | | 10x+x-2=-90 | | 5n+(-6)=-2 | | 36-4v-3c=22 | | (3-4x)-3(2.4x-7)= | | x+8=6x+3 | | -17x=-12 | | 5+4x=x-6 | | 2753-3456+13= | | 2(x-7)=327 | | 2nm+5=3 |